Lactic Acid Bacteria in Finfish—An Update - Ringø, Einar; Hoseinifar, Seyed Hossein; Ghosh, Koushik; Doan, Hien Van; Beck, Bo Ram; Song, Seong Kyu (Frontiers in Microbiology, 2018)
A complex and dynamic community of microorganisms, play important roles within the fish gastrointestinal (GI) tract. Of the bacteria colonizing the GI tract, are lactic acid bacteria (LAB) generally considered as favorable microorganism due to their abilities to stimulating host GI development, digestive function, mucosal tolerance, stimulating immune response, and improved disease resistance. In early finfish studies, were culture-dependent methods used to enumerate bacterial population levels within the GI tract. However, due to limitations by using culture methods, culture-independent techniques have been used during the last decade. These investigations have revealed the presence of Lactobacillus, Lactococcus, Leuconostoc, Enterococcus, Streptococcus, Carnobacterium, Weissella, and Pediococcus as indigenous species. Numerous strains of LAB isolated from finfish are able to produce antibacterial substances toward different potential fish pathogenic bacteria as well as human pathogens. LAB are revealed be the most promising bacterial genera as probiotic in aquaculture. During the decade numerous investigations are performed on evaluation of probiotic properties of different genus and species of LAB. Except limited contradictory reports, most of administered strains displayed beneficial effects on both, growth—and reproductive performance, immune responses and disease resistance of finfish. This eventually led to industrial scale up and introduction LAB-based commercial probiotics. Pathogenic LAB belonging to the genera Streptococcus, Enterococcus, Lactobacillus, Carnobacterium, and Lactococcus have been detected from ascites, kidney, liver, heart, and spleen of several finfish species. These pathogenic bacteria will be addressed in present review which includes their impacts on finfish aquaculture, possible routes for treatment. Finfish share many common structures and functions of the immune system with warm-blooded animals, although apparent differences exist. This similarity in the immune system may result in many shared LAB effects between finfish and land animals. LAB-fed fish show an increase in innate immune activities leading to disease resistances: neutrophil activity, lysozyme secretion, phagocytosis, and production of pro-inflammatory cytokines (IL-1β, IL-6, IL-8, and TNF-α). However, some LAB strains preferentially induces IL-10 instead, a potent anti-inflammatory cytokine. These results indicate that LAB may vary in their immunological effects depending on the species and hosts. So far, the immunological studies using LAB have been focused on their effects on innate immunity. However, these studies need to be further extended by investigating their involvement in the modulation of adaptive immunity. The present review paper focuses on recent findings in the field of isolation and detection of LAB, their administration as probiotic in aquaculture and their interaction with fish immune responses. Furthermore, the mode of action of probiotics on finfish are discussed.